БЕЛАНОВСКИЙ В.Н., ИВАНОВА О.Е., ИВАШКЕВИЧ В.И., СТЕЦКЕВИЧ С.М., ЧЕКАНОВА г.п. и ЯКУБОВСКИЙ В.А. Очерки истории южных и западных славян. Л.,1957 - Петровський , О.О. (Український історичний журнал, 2024)
.